THE INFLUENCE OF PROFIT, CASH FLOW, LIQUIDITY, LEVERAGE ON SHARE PRICE IN LQ45 COMPANIES - Erwin Yesayas Manalu; Nina Purnasari; Romasi Habeahan; Ulfa Nurhayani (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
This study aims to examine and analyze how the influence of Profit, Cash Flow, Liquidity, Leverage on Stock Prices in IQ45 Companies Listed on the Stock Exchange Indonesia for the period 2018 – 2021. This research has a population of 45 companies and a sample of 29 companies. The research method uses quantitative research. The data used is secondary data. Purposive sampling is a research sampling technique. Data analysis techniques used is multiple linear regression analysis. The results of the study show that partially leverage has a significant effect on stock prices, while profit, cash flow and liquidity have no and no significant effect on stock prices and simultaneously profit, cash flow, liquidity and leverage have a significant effect on stock prices .